Circular RNA lipid nanoparticle vaccine against SARS-CoV-2 - Kelsey L. Swingle; Alex G. Hamilton; Xuexiang Han; Kuo-Chieh Liao; Hannah C. Safford; Ajay S. Thatte; Hannah C. Geisler; Junchao Xu; Tzuen Yih Saw; Yue Wan; Michael J. Mitchell (Proceedings of the National Academy of Sciences, 2025)
With the advent and widespread use of messenger RNA (mRNA) vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), RNA vaccines have emerged as an exciting class of vaccine offering low cost, rapid development, and high modularity and manufacturability. Protein-coding circular RNA (circRNA) is an emerging class of RNA cargo that offers increased stability compared to mRNA with potentially reduced immunogenicity, but delivery technologies for intracellular delivery of circRNA remain underexplored. Here, we develop an optimized lipid nanoparticle (LNP) platform for circRNA delivery to immune cells, observing strong and durable transgene expression in vitro and in vivo. We employ a design-of-experiments (DoE) methodology to identify key formulation parameters for enhanced circRNA delivery and, upon intramuscular administration of our optimized circRNA LNPs to mice, observe substantial accumulation within draining lymph nodes and strong dendritic cell (DC) maturation at short time points. Applying this optimized circRNA LNP platform to vaccination against SARS-CoV-2, we demonstrate robust antibody production and enhanced immune responses in mice compared to vaccination with mRNA LNPs, including strong T h 1-biased cellular responses and a 3.8-fold increase in antigen-specific reciprocal endpoint IgG titers. These results provide insights into design criteria for circRNA LNP formulations and support the use of circRNA LNPs for vaccination against infectious diseases.